The Use of PhET Interactive Simulations and VASCAK with QR Code Leaflet-Virtual Laboratory to Enhance Digital Literacy Skills of High School Physics Teachers in South Solok Regency - Zulhendra, Zulhendra (Pelita Eksakta, 2025)
The rapid advancement of technology in the era of Industry 4.0 and Society 5.0 has made digital literacy an essential skill for teachers. As Generation Z is increasingly immersed in the digital world, teachers must possess digital literacy to deliver innovative learning experiences. Virtual laboratories, such as PhET Interactive Simulations and VASCAK, provide a solution for schools with limited resources. Observations at 11 high schools in South Solok Regency revealed that practical work is hindered by a lack of equipment and materials. Many teachers are unfamiliar with virtual labs, and even those who are aware struggle with understanding the tools. Furthermore, teachers rarely use practical modules that students can use for independent learning. To address this, a Technical Guidance program was implemented to introduce virtual laboratories and improve teachers' digital literacy. Evaluations using pre-test and post-test methods showed a significant improvement, with a normalized gain of 0.73, indicating high progress in teachers' competencies.